2009
DOI: 10.1002/da.20533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medication and psychotherapy on heart rate variability in panic disorder

Abstract: Our study replicated the finding that increased HR and decreased HRV occur in PD patients. Given the evidence of cardiac risk related to HRV, CBT appears to have additional benefits beyond symptom reduction. The mechanisms of this difference between CBT and sertraline are unclear and require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 58 publications
(48 reference statements)
1
49
0
2
Order By: Relevance
“…Seven studies with Panic Disorder patients were found, four randomized (Meuret et al, 2012;Craske et al, 2005;Riley et al, 1995;Roth et al, 1987), two controlled trials (Garakani et al, 2009;Mussgay and Rüddel, 2004) and one open study (Ehlers et al, 1995).…”
Section: Panic Disorder With or Without Agoraphobiamentioning
confidence: 99%
“…Seven studies with Panic Disorder patients were found, four randomized (Meuret et al, 2012;Craske et al, 2005;Riley et al, 1995;Roth et al, 1987), two controlled trials (Garakani et al, 2009;Mussgay and Rüddel, 2004) and one open study (Ehlers et al, 1995).…”
Section: Panic Disorder With or Without Agoraphobiamentioning
confidence: 99%
“…Previous studies (Garakani et al, 2009;Martinez, Garakani, Kaufmann, Aaronson, & Gorman, 2010) found a significantly lowered pNN50% in panic disorders relative to controls, suggesting that more anxiety caused a decrease in pNN50%. This study also found a significant increase of the pNN50 from the post-compared to the pretreatment mpTSST, showing that participants had lower levels of anxiety during the posttreatment mpTSST.…”
Section: Sdnnmentioning
confidence: 75%
“…Interestingly, patients with depression and several forms of anxiety disorder have evidence of reduced heart rate variability. Others and we have shown that effective cognitive behavioral therapy for patients with panic disorder also results in an increase in high frequency heart period variability, representing an improvement in parasympathetic control over cardiovascular physiology [2]. Thus the well-known links between psychiatric illness and risk for heart disease may be similarly mediated at least in part by ANS imbalance and be susceptible to behavioral interventions.…”
mentioning
confidence: 74%